The Relationship between Reading Interest and the Ability to Solve Mathematics Story Problems in Elementary School Students - Ismi Nafisah, Azizah; Bisri , Moh (UIN Raden Mas Said Surakarta, 2024)
Reading is the main key to understanding the content of reading texts. Reading activities can be done according to someone's interest. A lack of interest in reading causes a lack of understanding of the content of the reading text. This research aims to determine the relationship between interest in reading and the ability to solve math story problems. This research uses quantitative correlational. The population used was 198 class V students in Gatak District, with a sample of 126 students. The sampling technique uses cluster random sampling. The instruments used in data collection were essay tests to measure the ability to solve mathematical problems and questionnaires to measure interest in reading. The data analysis technique used in this research is product-moment correlation. The results showed that interest in reading was in the moderate category for 69 students, or around 55% of 126 students, while students' ability to solve math story problems was in the medium category for 71 students, or around 56% of 126 students. A sig value was obtained based on hypothesis test calculations using SPSS 23. 0.000 < 0.05, then there is a correlation between variables showing a positive relationship between interest in reading and students' ability to solve math story problems. Schools are expected to improve students' abilities in solving mathematical story problems through motivation and habituation to increase interest in reading